Homozygous deleterious variants in MYCBPAP induce asthenoteratozoospermia involving abnormal acrosome biogenesis, manchette structure and sperm tail assembly in humans and mice - Yiling Zhou; Chaofeng Tu; Charles Coutton; Jianan Tang; Shixiong Tian; Shuyan Tang; Guillaume Martinez; Dapeng Zhou; Célia Tebbakh; Jiaxiong Wang; Raoudha Zouari; Xuehai Zhou; et al. (Science China Life Sciences, 2025)

Bi-allelic truncating variants in CFAP206 cause male infertility in human and mouse - Qunshan Shen; Guillaume Martinez; Hongbin Liu; Julie Beurois; Huan Wu; Amir Amiri-Yekta; Dan Liang; Zine-Eddine Kherraf; Marie Bidart; Caroline Cazin; Tristan Celse; Véronique Satre; et al. (Human Genetics, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: A missense mutation in IFT74, encoding for an essential component for intraflagellar transport of Tubulin, causes asthenozoospermia and male infertility without clinical signs of Bardet–Biedl syndrome - Patrick Lorès; Zine-Eddine Kherraf; Amir Amiri-Yekta; Marjorie Whitfield; Abbas Daneshipour; Laurence Stouvenel; Caroline Cazin; Emma Cavarocchi; Charles Coutton; Marie-Astrid Llabador; Christophe Arnoult; Nicolas Thierry-Mieg; et al. (Human Genetics, 2021)

A missense mutation in IFT74, encoding for an essential component for intraflagellar transport of Tubulin, causes asthenozoospermia and male infertility without clinical signs of Bardet–Biedl syndrome - Patrick Lorès; Zine-Eddine Kherraf; Amir Amiri-Yekta; Marjorie Whitfield; Abbas Daneshipour; Laurence Stouvenel; Caroline Cazin; Emma Cavarocchi; Charles Coutton; Marie-Astrid Llabador; Christophe Arnoult; Nicolas Thierry-Mieg; et al. (Human Genetics, 2021)

Genetic analyses of a large cohort of infertile patients with globozoospermia, DPY19L2 still the main actor, GGN confirmed as a guest player - Tristan Celse; Caroline Cazin; Flore Mietton; Guillaume Martinez; Delphine Martinez; Nicolas Thierry-Mieg; Amandine Septier; Catherine Guillemain; Julie Beurois; Antoine Clergeau; Selima Fourati Ben Mustapha; Mahmoud Kharouf; et al. (Human Genetics, 2021)

The genetic architecture of morphological abnormalities of the sperm tail - Aminata Touré; Guillaume Martinez; Zine-Eddine Kherraf; Caroline Cazin; Julie Beurois; Christophe Arnoult; Pierre F. Ray; Charles Coutton (Human Genetics, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Single cell co-amplification of polymorphic markers for the indirect preimplantation genetic diagnosis of hemophiliaA, X-linked adrenoleukodystrophy, X-linked hydrocephalus and incontinentia pigmenti loci on Xq28 - Nadine Gigarel; Nelly Frydman; Pierre F. Ray; Violaine Kerbrat; Julie Steffann; Ren Frydman; Arnold Munnich; Philippe Burlet (Human Genetics, 2004)